Current Trends in Mixed-Methods Research Designs, Methodological Limitations, and Future Directions: A Systematic Review - Tamang, Min; Adhikari, Devendra; Makane, Anjali (NPRC Journal of Multidisciplinary Research, 2026)
Background: The development of mixed-methods research design as the “third paradigm” in educational research has gained momentum as it integrates qualitative and quantitative approaches to generate deeper insights. However, the selection of research designs, their methodological limitations, and their potential for further development require systematic investigation. Purpose: This paper systematically examines trends in mixed-methods research designs and their methodological limitations from 2022 to March 2026. It addresses: (RQ1) the most commonly used research designs; (RQ2) the reported methodological limitations; and (RQ3) suggested future research directions. Methods: Using Snyder’s (2019) model and the PRISMA 2020 criteria, the literature search was conducted across Sage Journals, Google Scholar, and Wiley Online Library using a Boolean search strategy. Of the 18,658 articles initially identified, 86 were included after screening and eligibility assessment. The analysis involved independent coding by three authors using Braun and Clarke’s (2006) six-phase framework, with iterative refinement to ensure inter-coder consistency. Categories were not mutually exclusive, allowing studies to be coded under multiple design types and methodological issues. Findings: Within the included studies (N = 86), four mixed-methods design typologies were identified with overlapping classifications: convergent designs (n = 33, 38.4%), sequential explanatory designs (n = 11, 12.8%), sequential exploratory designs (n = 10, 11.6%), and hybrid/multi-phase designs (n = 28, 32.6%). Methodological limitations were grouped into sampling and contextual constraints (n = 47, 54.7%), design and analytical weaknesses (n = 36, 41.9%), measurement and data quality concerns (n = 28, 32.6%), integrative challenges (n = 21, 24.4%), and practical implementation challenges (n = 19, 22.1%). Future research directions emphasised larger sample sizes (n = 38, 44.2%), improved data quality (n = 32, 37.2%), enhanced methodological rigour (n = 28, 32.6%), theory development (n = 21, 24.4%), and stronger practical implications (n = 21, 24.4%). Conclusion: Convergent designs appear to be the most frequently identified mixed-methods approach within the reviewed studies. However, persistent weaknesses in design, measurement, and data integration continue to affect overall research rigour. The increasing use of hybrid designs further reflects growing methodological flexibility in addressing complex educational research problems.